1995
DOI: 10.1074/jbc.270.26.15762
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Charged Residues of Human Interleukin-5 in Receptor Binding and Cellular Activation

Abstract: Interleukin-5 (IL-5) is a cytokine that plays a major role in the differentiation and activation of eosinophils. In order to identify which charged residues of human IL-5 are important in binding to its receptor and subsequent cellular activation, we have systematically replaced all of the clusters of charged amino acids with alanine residues. The mutants have been expressed in Escherichia coli, renatured, and purified. They were assayed for ability to cause proliferation of the erythroleukaemic cell line TF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 41 publications
6
70
0
Order By: Relevance
“…The existing unique ClaI and DraIII restriction sites, which were 27 nucleotides upstream and 54 nucleotides downstream, respectively, of the CD loop DNA coding region in the IL-5 gene, were used to generate a randomly mutated cassette. This cassette was constructed from the following mutagenic oligonucleotides: primer CD101, 5Ј-ATACATCGATGGCCAAAAAAAAAAGTGTGGA(NNB) 5 GT-AAACCAATTCCTAGACTA-3Ј (ClaI site underlined); primer CD102, 2 P. Tsui, unpublished results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing unique ClaI and DraIII restriction sites, which were 27 nucleotides upstream and 54 nucleotides downstream, respectively, of the CD loop DNA coding region in the IL-5 gene, were used to generate a randomly mutated cassette. This cassette was constructed from the following mutagenic oligonucleotides: primer CD101, 5Ј-ATACATCGATGGCCAAAAAAAAAAGTGTGGA(NNB) 5 GT-AAACCAATTCCTAGACTA-3Ј (ClaI site underlined); primer CD102, 2 P. Tsui, unpublished results.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive site-directed mutagenesis studies have shown that residues clustered near the helix bundle interface, in the CD loop, including Glu 89 and Arg 91 , and at the carboxyl-terminal end of helix D, notably Glu 110 , engage in receptor ␣ chain binding (4 -6). Glu 13 , which is at each of the distal ends of the IL-5 cylinder away from the interface between the two four-helix bundles and is not involved directly in ␣ chain interaction, is a key residue mediating productive interaction of the ␤ c chain of IL-5 receptor (4,5). It is the ␤ c recruitment into ␣␤ c that leads to triggering of the intracellular signaling cascade.…”
Section: Human Interleukin-5 (Hil-5)mentioning
confidence: 99%
“…Binding of peptides to the IL-5R␣ ECD was measured by using a 125 I-IL-5 competition-binding assay in a scintillation proximity assay format (28). TF-1 cell-based radioligand-binding studies were carried out as described previously (19). In brief, TF-1 cells (1 ϫ 10 6 per point) were incubated with 200 pM 125 I-IL-5 (1,130 Ci͞mmol; 1 Ci ϭ 37 GBq) for 2 h at room temperature in the presence of increasing concentration of unlabeled cytokine or peptide.…”
Section: Methodsmentioning
confidence: 99%
“…A number of protein-based IL-5 antagonists have been reported, including soluble IL-5 receptor ␣ chains (IL5R␣s) that sequester the ligand in solution (15), single point mutants of IL-5 that occupy the receptor but fail to initiate receptor activation (16,17), and neutralizing antibodies directed against IL-5 (18). Detailed structure-function analysis of the IL-5͞IL-5 receptor interaction, by scanning alanine mutagenesis of IL-5, has revealed that the key charged residues important for the formation of the ligand-receptor complex are spatially distinct and are separated across a large surface area (17,19). This topography may provide a molecular explanation for the lack of small molecule IL-5 receptor antagonists that have been reported.…”
mentioning
confidence: 98%
“…IL5 is a symmetric homodimer in which each helical bundle domain is composed of three helices (A-C) from one chain and one (D) from the other (14). The binding epitope on IL5 for IL5R␣ is mapped on the structure, showing the importance of charged residues in helix B (His 38 , Lys 39 , and His 41 ), the CD turn (Glu 88 , Glu 89 , Arg 90 , and Arg 91 ), and helix D (Glu 110 ) for IL5R␣ binding (15)(16)(17). For ␤c binding and signal transduction, Glu 13 in helix A is thought to be a key residue (17).…”
mentioning
confidence: 99%